Rodent Pests and their Control in Poultry Farms of Jodhpur - Bhardwaj, Devendra (Annals of Arid Zone, 2016)
Nine poultry farms around Jodhpur city were surveyed. Indian gerbil, Tatera ind;ca was found to be the predominant species in the poultry farms situated away from human habitation followed by black rat, Rattus rattus. However, Rattus rattus was the predominant species of the poultry farms close to human habitation followed by Mus musculus. Poultry feed is recommended as the carrier of poison whenever rodent control operations are taken up in poultry farms.